2018
DOI: 10.1039/c8cp02749h
|View full text |Cite
|
Sign up to set email alerts
|

Understanding dissolution process of chitin crystal in ionic liquids: theoretical study

Abstract: Chitin is a promising biomass resource and has high potential for industrial applications owing to its huge annual production in nature. However, it exhibits poor processability and solubility due to its very stable and crystalline character. Recently, ionic liquids (ILs) have attracted attention as solvents for structural polysaccharides - for example, 1-allyl-3-methylimidazolium bromide (AMIMBr) has been found to dissolve chitin. As few ILs are known to dissolve chitin, little research has been conducted on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…As mentioned earlier, the large number of hydrogen bonds in chitin-based biopolymers lead to difficulties in the dissolution and degradation of chitin and chitosan. Ionic liquids exhibit the ability to cleave hydrogen bonds in polysaccharides and form new hydrogen bonds between anions and the hydroxyl groups of biopolymers, improving the dissolution [30,31].…”
Section: Ionic Liquid As Catalystmentioning
confidence: 99%
“…As mentioned earlier, the large number of hydrogen bonds in chitin-based biopolymers lead to difficulties in the dissolution and degradation of chitin and chitosan. Ionic liquids exhibit the ability to cleave hydrogen bonds in polysaccharides and form new hydrogen bonds between anions and the hydroxyl groups of biopolymers, improving the dissolution [30,31].…”
Section: Ionic Liquid As Catalystmentioning
confidence: 99%
“…Therefore, acetate ions can be more effective than chloride or dimethylphosphate anions. Studies involving a molecular dynamics (MD) approach to evaluate the dissolution of chitin crystals in imidazolium-based ILs revealed that the solubility of chitin can be correlated with the number of intermolecular hydrogen bonds by acetamido groups in the chitin crystal [55]. The data also proved that mixing a small amount of 2-bromoethyl acetate, as a bromide generator, with (Amim)(Br)can enhance chitin solubility.…”
Section: Chitinmentioning
confidence: 99%
“…The chitin is constituted of β (1→4) linked residues of N-acetyl-2-amino-2-deoxy- d -glucose and 2-amino-2-deoxy- d -glucose ( Elieh-Ali-Komi & Hamblin, 2016 ). It exhibits an extremely poor aqueous solubility due to its highly crystalline characteristics which are brought about via hydrogen bonding between the acetamido moieties ( Uto et al, 2018 ; Zhu et al, 2016 ). The partially deacetylated chitin is water-soluble ( Muzzarelli et al, 1999 ; Ying et al, 2011 ).…”
Section: Chitosanmentioning
confidence: 99%